Craniovertebral Junction Meningiomas: Analysis of Clinical and Radiological Results. Issue 1 (April 2016) - Raco, Antonino; Pesce, Alessandro; Toccaceli, Giada; Frati, Alessandro; Dugoni, Demo Eugenio; Delfini, Roberto
Introduction: Craniovertebral junction (CVJ) meningiomas are lesions of complex surgical management for the delicate anatomical structures involved and for their tendency to encase/dislocate vital structures such as the vertebrobasilar system and the lower cranial nerves. Matherials and Methods: We analized sex, age, clinical presentation, topography, surgical approach, Simpson Grade Resection, Lower Cranial Nerves postoperative deficit and radiological, histology and clinical follow up at 1, 12 and 24 months of 61 patients affected by CVJ meningiomas, operated on in the Neurosurgical Divisions of the University of Rome "Sapienza" from 1997 to 2013. Results: 78.7% of patients were women (mean age 52.85 years); the onset symptom was pain in 65.5% of cases. The mean preoperative Nurick grade of the sample was 3, 78; The most frequent histological type was endotheliomatous (42.8%). Twenty-two patients (5 with lateral and 17 posterolateral axial topography) were treated with posterior median approach; in 39 cases (30 anterolateral and 9 anterior) we performed a posterolateral approach. A Gross Total Removal was achieved in 85.2% of cases. We reported an average neurological improvement in this series (average preoperative Nurick 3.81 and at 12 months 2.13). In 29 patients there was a transient deficit of IX, X and XI cranial nerves. No statistically significant association between surgical approach and temporary or permanent postoperative complications has been found. Conclusions: In conclusion posterior and posterolateral with/without condilectomy and transposition of VA approaches represents the gold standard for the surgical removal of these tumors and are safe and effective in terms of postoperative morbidity.